Corn particle size and pelleting influence on growth performance, fecal shedding, and lymph node infection rates of salmonella enterica serovar typhimurium - Barker, M.R.; Minton, J. Ernest; DeRouchey, Joel M.; Bond, K.M.; Lee, D.J.; Burkey, T.E.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Ninety-six pigs (initially 13.8 lb.) were used in a 28-d trial to determine the interactive effects between pelleting and particle size on Salmonella serovar Typhimurium shedding and colonization in a young growing pig model. The experiment was a 2 × 2 factorial arrangement consisting of meal or pelleted diets with fine or coarse ground corn. Pigs were fed the diets 1 wk pre-salmonella inoculation and allotted based on weight to one of four dietary treatments. For the main effect of particle size, pigs fed finer ground corn had significantly improved feed efficiency (P<0.01) than pigs fed coarser ground corn for the 28 d trial. Pigs fed meal diets had greater ADG, ADFI, and improved F/G (P<0.05) than the pigs fed pelleted diets. Fecal shedding of salmonella was low and variable, with no significant differences between main effects (P<0.26) or in treatments (P>0.82). There was no difference in salmonella infection rates of mesenteric lymph nodes obtained on d 28 between treatments or main effects. Finer grinding and meal diets generally improved growth, feed intake, and feed efficiency compared to pigs fed coarser ground or pelleted feeds. However, particle size or diet form did not alter fecal shedding or mesenteric lymph node infection rates of salmonella organisms in our study.
Keywords: Weanling pigs; Disease challenge; Salmonella; Particle size; Pelleting; Swine